Oxygraphis delavayi Franchet (Ranunculaceae): a new generic record for Arunachal Pradesh and a new species record for India - Umeshkumar L. Tiwari (Journal of Threatened Taxa, 2016)
Oxygraphis delavayi Franch. (Ranunculaceae) is an endemic plant species occurring in China.  It is reported here for the first time from India.  A detailed description, herbarium image and relevant notes are provided for its collection and identification.